IMPLEMENTASI POLA MAKAN SEHAT PADA ANAK USIA DINI DI KB DAN TK ISLAM NURUL HUDA WONOREJO KENCONG KABUPATEN JEMBER - Izatul Milla; Rahmawati, Lailatul; Laili, Ayik Nikmatul (Forind Press, 2025)
Meeting the nutritional needs of young children remains a serious challenge, particularly in rural areas such as the Kencong subdistrict in the Jember regency, where the prevalence rate of stunting is 29.7%. This situation is exacerbated by modern lifestyles and low nutritional literacy among parents, resulting in unhealthy eating patterns. This study aims to examine the implementation of healthy eating patterns at Nurul Huda Wonorejo Kencong Islamic Kindergarten and Preschool and to identify the factors that support or hinder this implementation. The research method employed is descriptive and qualitative, taking an interpretative approach. Data were collected through participatory observation, semi-structured interviews and documentation from school principals, teachers and parents of students. The results of the study indicate that the school has successfully established a culture of healthy eating through policies such as providing nutritious packed lunches, banning instant foods, holding monthly parenting sessions, providing group meals and encouraging active parental involvement. However, challenges remain, including low nutritional literacy among some parents, the absence of nutrition experts, and limited school kitchens. The success of this programme highlights the importance of collaboration between schools, parents and professionals in promoting healthy eating habits from an early age. The programme is in line with national policies such as GERMAS and could be replicated in other early childhood education institutions.